2017
DOI: 10.1093/bioinformatics/btx743
|View full text |Cite
|
Sign up to set email alerts
|

The OncoPPi Portal: an integrative resource to explore and prioritize protein–protein interactions for cancer target discovery

Abstract: andrey.ivanov@emory.edu or hfu@emory.edu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 58 publications
1
51
0
Order By: Relevance
“…Bioinformatics analyses, including usage of microarray expression datasets (Stuart, Segal, Koller, & Kim, 2003), protein/gene-protein/gene interaction networks (Ivanov et al, 2018), and the annotation of genes (Phuong & Nhung, 2013), are being utilized as a powerful tool to study the cancer progression and to identify serum biomarkers (Hormigo et al, 2006;Huddleston, Wong, Welch, Berkowitz, & Mok, 2005) as well as potential therapeutic targets (Armstrong et al, 2003;Ye et al, 2003). Large amounts of data generated by this tool are collected in public archives such as the major public projects The Cancer Genome Atlas (TCGA) (DeSantis, Ma, Bryan, & Jemal, 2014), Oncomine (Rhodes et al, 2004), Gene Expression Omnibus (GEO) (Barrett et al, 2013), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics analyses, including usage of microarray expression datasets (Stuart, Segal, Koller, & Kim, 2003), protein/gene-protein/gene interaction networks (Ivanov et al, 2018), and the annotation of genes (Phuong & Nhung, 2013), are being utilized as a powerful tool to study the cancer progression and to identify serum biomarkers (Hormigo et al, 2006;Huddleston, Wong, Welch, Berkowitz, & Mok, 2005) as well as potential therapeutic targets (Armstrong et al, 2003;Ye et al, 2003). Large amounts of data generated by this tool are collected in public archives such as the major public projects The Cancer Genome Atlas (TCGA) (DeSantis, Ma, Bryan, & Jemal, 2014), Oncomine (Rhodes et al, 2004), Gene Expression Omnibus (GEO) (Barrett et al, 2013), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the OncoPrint genes, 65 (89%) nodes integrated this network (Figure 5A). On the other hand, out of the 258 genes that make up our String PPi network, 16 (6%) genes and 18 edges were part of the OncoPPi BC network 53,54 . The degree centrality made it possible to establish a significant correlation (Spearman p < 0.05) between our String PPi network and the OncoPPi BC network (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study [44], we revealed essential proteins associated with BC pathogenesis through deep analyses of genetic alterations, signaling pathways [52], protein-protein interaction networks [55, 56], protein expression [57, 58], dependency maps [57], and enrichment maps [49] of previously prioritized genes by the Consensus Strategy [59], the Pan-Cancer Atlas project [6064], the Pharmacogenomics Knowledgebase (PharmGKB) [2], and the Cancer Genome Interpreter [65]. The druggable prediction of BC proteins through ML approaches will provide us relevant information regarding potential biomarkers, therapeutic targets and future clinical trials, avoiding ethnicity bias and improving cancer pharmacogenomics and precision medicine worldwide [6676].…”
Section: Resultsmentioning
confidence: 99%